Thermal challenges of sport performance at altitude: from human thermoregulation to technical solutions for thermal protection - Filingeri, D. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
The ability to optimally regulate body temperature is key to ensure appropriate physiological function that can sustain exercise performance. Performing at altitude and under cold stress poses an additional challenge to the thermoregulatory and cardiovascular systems, and this is well known to be a key driver of performance decrements. An understanding of the physiology of human autonomic and behavioural thermoregulation during exercise and of the thermal protection strategies available to maintain performance under cold stress is therefore essential to ensure athletes are fully prepared to perform under thermal stress. The aim of this talk is to provide an overview of the human thermoregulatory system, with emphasis on the mechanisms of skin temperature and wetness sensing that support behavioural thermoregulation at rest and during exercise. The implications of these fundamental insights will be discussed in the context of their application to optimize the design of sport and protective clothing aimed at optimizing exercise performance in the cold.